2018
DOI: 10.1016/j.matbio.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric protein identification of dystrophic, Pierson and other laminin polymerization residues

Abstract: Laminin polymerization is a key step of basement membrane self-assembly that depends on the binding of the three different N-terminal globular LN domains. Several mutations in the LN domains cause LAMA2-deficient muscular dystrophy and LAMB2-deficient Pierson syndrome. These mutations may affect polymerization. A novel approach to identify the amino acid residues required for polymerization has been applied to an analysis of these and other laminin LN mutations. The approach utilizes laminin-nidogen chimeric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…22,23,47,48 The mechanism of reduced LAMB2-Del44 quantity in the GBM was not investigated, leaving the possibility of decreased secretion unsolved, in which case overexpression should improve the Del44 phenotype. However, we note that in vitro data suggested that LAMB2-R246Q is both secretion-and polymerization-defective, 28 and might require some degree of both increased expression and polymerization for complete function. In line with this hypothesis, relatively high LAMB2-R246Q overexpression abrogated aberrant capillary loop GBM LAMB1 and podocyte desmin expression but did not completely prevent proteinuria.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…22,23,47,48 The mechanism of reduced LAMB2-Del44 quantity in the GBM was not investigated, leaving the possibility of decreased secretion unsolved, in which case overexpression should improve the Del44 phenotype. However, we note that in vitro data suggested that LAMB2-R246Q is both secretion-and polymerization-defective, 28 and might require some degree of both increased expression and polymerization for complete function. In line with this hypothesis, relatively high LAMB2-R246Q overexpression abrogated aberrant capillary loop GBM LAMB1 and podocyte desmin expression but did not completely prevent proteinuria.…”
Section: Discussionmentioning
confidence: 67%
“…In an established in vitro assay, laminin polymerization mediates laminin retention on Schwann cells (SCs) via receptors in the cell membrane. 24,[27][28][29][30] Our previous investigation of LAMB2-S83R indicated an approximately 50% reduction in retention of LM-121 heterotrimers containing LAMB2-S83R on SCs relative to wild-type (WT) LM-121. 24 The location of S83R within the Del44 deleted sequence predicts further impairment of laminin polymerization of LM-121 containing LAMB2-Del44.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a subset of Pierson syndrome patients, the disease results from laminin β2LN mutations that cause a failure of laminin polymerization (Funk et al, 2017). Polymerization can be restored by βLNNd, a homolog of αLNNd that enables polymerization of laminins with βLN mutations (McKee et al, 2018). In Alport syndrome, there is a reduction of disulfide covalent crosslinked collagen due to loss of α3/α4/α5-collagen-IV (Gunwar et al, 1998).…”
Section: Future Studiesmentioning
confidence: 99%